Penal repression for breaches of IHL: probing the “Boko Haram” war crimes and crimes against humanity / Abdulrashid Lawan Haruna, Mohammed Naqib Ishan Jan and Mohammad Hisham Mohammad Kamal - Lawan Haruna, Abdulrashid; Ishan Jan, Mohammed Naqib; Mohammad Kamal, Mohammad Hisham (2014)
International humanitarian law (IHL) requires States Parties to the Geneva Conventions and the Additional Protocols to enact penal legislations in their domestic legal systems for the purpose of repressing and suppressing violations of the law committed in their territories. The law considers penal repression for violations of IHL as one of the mechanisms through which the law can be enforced. IHL does not seek to prosecute every violation of its rules but seeks to prosecute grave breaches of the Geneva Conventions and the Protocols as well as serious violations of the laws and customs applicable in armed conflicts. Boko Haram as an armed group engaged in fighting the Government of Nigeria and seeks to establish Islamic state in the country is alleged to have committed several breaches of IHL. Therefore, this article intends to examine the grave breaches of the Geneva Conventions and the Protocols committed by Boko Haram in the conflict in Northern Nigeria. It equally examines other serious violations of the laws and customs applicable in armed conflicts that were committed by Boko Haram. The article posits that the violations of the rules of IHL committed by Boko Haram constitute among other crimes the core international crimes of war crimes and crimes against humanity. The perpetrators of such crimes deserve to be prosecuted and the commission of the crimes must equally be suppressed. It is recommended that members of Boko Haram who perpetrate the core international crimes should be held responsible and be allowed to face the full wrath of the law through penal repression.